Niat Pelaku Intrapreneurship dan Organisasi terhadap Kinerja Keuangan UMKM di Kota Denpasar - I Gede Agus Mas Pragiva Muscaya; Ni Luh Kardini; Komang Asri Pratiwi (Mutiara: Jurnal Ilmiah Multidisiplin Indonesia, 2024)
This study aims to determine the effect of intrapreneurship and organization on the financial performance of MSMEs (Micro, Small And Medium) in Denpasar City. This study uses a qualitative method. The MSME population in Denpasar City reached 32,476 MSMEs and the sample used was 100 MSMEs in Denpasar city. This study uses data collection techniques by distributing questionnaires. Validity and reliability tests were carried out on respondents who owned MSMEs in Denpasar City. The results of the t test can be obtained t-count of the Intrapreneurship variable of 1.231 with a significance value of 0.221. This significance value is greater than the significance limit value, which is equal to 0.05. Means that Intrapreneurship has a positive and insignificant effect on Financial Performance. The results of the t test can be obtained by the t-count value of the Organizational variable of 5.052 with a significance value of 0.000. This significance value is smaller than the significance limit value, which is equal to 0.05. Means the organization has a positive and significant effect on financial performance. Based on the results of the F test, the F value is 20.324 with a significance level of 0.000, so simultaneously the Intrapreneurship and Organization variables have a significant effect on the Financial Performance variable. As well as from the test results of the coefficient of determination, the R Square value shows a value of 0.295 or 29.5% indicating that the ability of the independent variable to explain the effect on the dependent variable and the remaining 70.5% can be explained by other variables outside of the research variable.